Implementasi Prinsip 3R Dalam Pengelolaan Sampah Rumah Tangga di Desa Gattareng, Kabupaten Bulukumba - Rafidah, Rafidah; Rahmayanti, Rahmayanti; Haderiah, Haderiah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
One effort to reduce the volume of waste in household settings is by implementing waste management levels. The level of waste management is waste management training, with an emphasis on reducing waste at the source (reduce), (reuse) activities, as well as (recycle) which will be processed if the waste cannot be reused. The aim of this research is to determine the waste management carried out by housewives through 3R in reducing waste generation in Gattareng Village, Kab. Bulukumba. The type of research used is descriptive analytical observation with a qualitative approach. The samples taken were 136 housewives. The results of the research that has been carried out are that all housewives in Gattareng Village, Kab. Bulukumba applies the 3R principle (reduce, reuse, recycle). However, the reduction actions that are not carried out at all are one of which is not rejecting the use of plastic 100%, then the reuse action that is carried out the least is using paper waste that is still 84.5% clean, and the recycling action that is not carried out at all is one of them does not make 100% compost. The waste generated was 0.692 kg/person/day and the largest waste composition was organic waste 2,094 kg (70%) and inorganic waste 879.83 (30%). The conclusion from this research is that all housewives in Gattareng Village, Kab. Bulukumba has implemented the 3R principle (Reduce, Reuse, Recycle). The suggestion from this research is to create a Waste Bank so that people can collect their waste